#TITLE_ALTERNATIVE# - NUR BUWANA (NIM: 13205007), HADYAN
Multilevel inverters are promised to provide a better performance in high power applications. A new modular multilevel inverter is proposed in this research. The proposed inverter is designed to combine the goodness of two previous topologies. Comparison between the proposed and the existing topology is the main topic to discuss in this research. To clarify the comparison aspect, all of the topologies are conceptually applied as a reactive power compensator (STATCOM) with reactive power rating of 10 MVAR and installed in the distribution system of 20 kV. It is shown that the proposed topology results in better performance than other topologies. Several simulated results are included to verify the proposed concept.